Safety and Efficacy of Intravitreal Chemotherapy (Melphalan) to Treat Vitreous Seeds in Retinoblastoma - Yacoub A. Yousef; Mays Al Jboor; Mona Mohammad; Mustafa Mehyar; Mario D. Toro; Mario D. Toro; Rashed Nazzal; Qusai H. Alzureikat; Magdalena Rejdak; Mutasem Elfalah; Iyad Sultan; Robert Rejdak; et al. (Frontiers in Pharmacology, 2021)
Background: Active vitreous seeds in eyes with retinoblastoma (Rb) adversely affects the treatment outcome. This study aimed to investigate the safety and efficacy of intravitreal melphalan chemotherapy (IViC) as a treatment for recurrent and refractory vitreous seeds in patients with Rb.Methods: We used a retrospective non-comparative study of patients with intraocular Rb who had vitreous seeds and were treated by IViC (20–30 μg of melphalan) using the safety-enhanced anti-reflux technique. Tumor response, ocular toxicity, demographics, clinical features, and survival were analyzed.Results: In total, 27 eyes were treated with 108 injections for recurrent (16 eyes) or refractory (11 eyes) vitreous seeds after failed systemic chemotherapy. A total of 15 (56%) were males, and 20 (74%) had bilateral disease. At diagnosis, the majority (n = 21) of the injected eyes were group D, and n = 6 were group C. Vitreous seeds showed complete regression in 21 (78%) eyes; 100% (n = 10) for eyes with focal seeds; 65% (n = 11/17 eyes) for eyes with diffuse seeds (p = 0.04); 7 (64%) eyes with refractory seeds; and 14 (87%) eyes with recurrent seeds showed complete response (p = 0.37). In total, 16 (59%) eyes developed side effects: retinal toxicity (48%), pupillary synechiae (15%), cataracts (30%), iris atrophy (7%), and retinal and optic atrophy (4%). Only one child was lost to follow-up whose family refused enucleation and none developed orbital tumor recurrence or distant metastasis.Conclusion: IViC with melphalan is effective (more for focal than diffuse seeding) and a relatively safe treatment modality for Rb that can improve the outcomes of eye salvage procedures. However, unexpected toxicity can occur even with the standard dose of 20–30 μg.